Analisis Implementasi Alokasi Belanja Pendidikan dalam Meningkatkan Kualitas Sumber Daya Manusia di Kota Surabaya : Studi Kasus Tahun 2023-2024 - Almardlina Jantika Esyi; Tiara Silviana Putri; Shelsa Aurora Ferdina Hermawan; Zahwa Amelya Tourmaline (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
Education is the main pillar in improving the Human Development Index (HDI). With a significant contribution to the development of the quality of human resources, especially in Surabaya City, this study aims to analyze the implementation of education budget allocations in Surabaya City in encouraging equitable distribution of education quality, as well as identifying bureaucratic and technical obstacles that cause inequality between the central city and peripheral areas. This research uses the literature study method by utilizing secondary data from various official sources such as BPS, Bappeda, Education Office, BPK, Ministry of Education and Research, and local policies.